Talking nets : an oral history of neural networks - Anderson, James A.; Rosenfeld, Edward (Cambridge, Mass. : MIT Press, 1998)
Surprising tales from the scientists who first learned how to use computers to understand the workings of the human brain.
Introduction -- Jerome Y. Lettvin -- Walter J. Freeman -- Bernard Widrow -- Leon N. Cooper -- Jack D. Cowan -- Carver Mead -- Teuvo Kohonen -- Stephen Grossberg -- Gail Carpenter and Stephen Grossberg -- Michael A. Arbib -- James A. Anderson -- David E. Rumelhart -- Robert Hecht-Nielsen -- Terrence J. Sejnowski -- Paul J. Werbos -- Geoffrey E. Hinton -- Bart Kosko -- Glossary -- Index.
"A Bradford book."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Neural computers; Neural networks (Computer science); Scientists -- Interviews; Science; Pattern recognition systems; Physical sciences; Artificial intelligence; Neural Networks, Computer; Science; Pattern Recognition, Automated; Natural Science Disciplines; Artificial Intelligence; Mathematical Concepts; Phenomena and Processes; Information Science; Disciplines and Occupations; Computing Methodologies; Ordinateurs neuronaux; Réseaux neuronaux (Informatique); Scientifiques -- Entretiens; Sciences; Reconnaissance des formes (Informatique); Sciences physiques; Intelligence artificielle; sciences (philosophy); physical sciences; artificial intelligence; science (modern discipline); COMPUTERS -- Neural Networks; Science; Physical sciences; Pattern recognition systems; Artificial intelligence; Neural computers; Neural networks (Computer science); Scientists; Neurale netwerken; Interview; interviews; Interviews; Interviews (vorm); Interviews; Interviews